Blurring our Boundaries and Caring for Our Common Space: Cultural and Environmental Imperatives - Widodo, Johannes (2021)
International Seminar on the Power of Proximity Between East and West Timor: “Bridging the Social, Political, Economic, and Cultural Gaps